The Interconnection Between Pharmaceutical Development and Preclinical Research (Review) - I. N. Ampilogova; M. V. Karlina; V. G. Makarov; M. N. Makarova (Разработка и регистрация лекарственных средств, 2023)
Introduction. Pharmaceutical development of an innovative highly effective and competitive drug is a long and expensive process, the result of which is quite difficult to predict in advance. To speed up the entry of a new drug to the treatment and reduce the developer's material costs, it is advisable to include preclinical experiments in the process of creating a drug.Text. The purpose of this work is to create a justified approach to the implementation of laboratory pharmaceutical development involving in vivo studies. The inclusion of preclinical studies in the process of laboratory pharmaceutical development will eliminate the negative impact of pharmaceutical factors on the bioavailability of a drugs and avoid errors in the selection of excipients, as well as reduce material and time costs. The review presents examples that demonstrate the relevance of conducting preclinical experiments at different stages of pharmaceutical development. These examples made it possible to describe a clearer algorithm of actions in the laboratory pharmaceutical development of a new drug from the moment a drug candidate molecule is selected.Conclusion. Due to increase the probability of successful pharmaceutical development at initial stage, it is necessary to carry out pharmacokinetic and/or pharmacodynamic experiments to make it possible to develop a drug with an optimal pharmacokinetic profile, reduce the number of preclinical studies, the cost of development, and ensure successful translation of data into clinical practice.